The language of the Pentateuch translation in the Eupatorian printed edition from 1841 - Işık, Murat (Vilnius University Proceedings, 2024)
This paper provides an analysis of the language employed in the Pentateuch section of the Eupatorian print (Gözleve) edition, a comprehensive translation of the Old Testament into the Karaim language published in 1841. The objective of the study is to identify the specific Crimean Karaim variety employed in the translation through an examination of phonological, morphological, and lexical features. The analysis reveals that the translation displays features of both Crimean Kipchak Karaim and Crimean Turkish Karaim, and that the characteristics vary depending on the specific books and chapters of the edition.
Keywords: Karaim; Crimean Karaim; Bible translations; Gözleve Bible; Oghuzic; Kipchak